Positioning Control Of A 1-DOF Pneumatic Muscle Actuator (PMA) System With Modified PID Plus Feedforward Controller - Sakthi Velu, Vasanthan (2016)
The pneumatic muscle actuator (PMA) is a novel actuator which carries numerous advantages such as high strength and power/weight ratio, low cost, compact, clean and easy to maintain features. However, pneumatic muscle actuator has notable nonlinear characteristics, which makes it difficult to control. The purpose of this research is focused on experimental system development and parameter characterization of phenomenological modelling for commercially available Festo Fluidic Muscle Actuator. The model and parameters obtained from the characterization are validated in simulation and experimental platform. The major part of the research is focused on the framework of the modified PID plus feedforward control system, and its effectiveness in a 1 degree-of-freedom PMA system is experimentally demonstrated in comparison with a classical PID controller. The overall control system comprises of a feedforward controller and a modified PID controller in the feedback loop which designed based on the exact PMA system characteristics. The design procedure of the modified PID plus feedforward controller is practical and features easy design procedures. The usefulness and advantages of the proposed controller are shown via positioning and tracking motion experimental studies. Besides, this study also highlights the robustness of the modified PID plus feedforward controller by examining its performance in point-to-point and tracking motions in the presence of extra mass. In the robustness performance, the modified PID plus feedforward controller is compared with a classical PID control systems. The comparative experiments results illustrate that modified PID plus feedforward controller shows the significant motion performances as compared to the PID controller by maintaining steady state error between ±50μm. The framework used to develop the proposed controller is generally enough for further investigation in PMA motion control system, further improvement in terms of positioning accuracy and tracking motion could extend the